House dust mite allergen levels in Chiang Mai homes - Trakultivakorn M. (2014)
The quantitative assays for house dust mite (HDM) allergens provide a valid index of exposure and can be used for risk evaluation. We assessed group I HDM allergen levels in mattress and living room floor dust from 35 Chiang Mai homes and identified factors associated with high allergen levels. One-third of mattress and living room floor dust had group I HDM allergen levels of between 2-10 μg/g. Two-thirds of mattress dust and a small amount of living room floor dust had group I HDM allergen levels of over 10 μg/g. The geometric means of Der p I, Der f I and total group I allergens in mattress and living room floor dust were 8.61, 2.88, and 15.81 μg/g and 1.61, 0.27 and 2.43 μg/g, respectively. Mattresses made of kapok and rugs kept in the living room were associated with high group I allergen levels.